Merokok, ISPA HUBUNGAN ANTARA PERILAKU MEROKOK DENGAN DERAJAT KEPARAHAN INFEKSI SALURAN PERNAPASAN AKUT DI PUSKESMAS BUMIAJI - Endah Panca Lydia F (Jurnal Keperawatan Malang, 2017)
Abstract Acute respiratory infection (ARI) was a common health problem that had the potential to cause greater health problems. One causes of ARI was the presence of members who smoke. This study aimed to determine the relationship between smoking behavior with the severity degree of ARI. It used observational analytic research using cross-sectional approach to adult patients at Puskesmas Bumiaji. The sample was chosen by Purposive Sampling and resulting 82 respondents. The variables measured were smoking behavior and ARI. The data was analyzed using spearman test with the result of p=0,000 (p>0.05). The conclusion of this study was that there was a relationship between smoking behaviors with acute respiratory infection. Keywords: smoking behavior, severity degree, acute respiratory infection (ARI).